Assessment of Knowledge on Prevention of Varicose Veins among the Security Guards at a Selected Security Recruitment Agency with a View to Develop an Information Booklet at Mangaluru - Sunitha Priya Menzes (RGUHS Journal of Nursing Sciences)
Background and objectives Millions of workers spend majority of their working days on their feet and many hours in static positions. Prolonged standing causes muscles to strain while the blood remains in the legs feet and cannot circulate properly. This results in inflammation of the veins and over a period of time this can progress to varicose veins. The study was conducted to assess the knowledge on prevention of varicose veins among the security guards by using a structured questionnaire.Methods Descriptive design was used for the study. A non probability purposive sampling technique was used to select 60 security guards from a selected security recruitment agency. The investigator assessed the knowledge regarding prevention of varicose veins using demographic proforma and a structured knowledge questionnaire. Following this an information booklet was administered to the subjects. The collected data were analysed using descriptive and inferential statistics.Results Mean pretest knowledge score was found to be 13.4plusmn5.07. There was a significant association between knowledge scores and demographic variables such as age education status and previous information T 3.84 at 0.05 level of significance. H1 was accepted and H0 was rejected. No significant association was found between knowledge scores and demographic variables such as gender religion work experience monthly income working hours and source of information T3.84 at 0.05 level of significance. Hence HO was accepted and H1 was rejected.Conclusion The information booklet was effective in enhancing the knowledge among security guards regarding the prevention of varicose veins. The results of the present study show that there is a great need for increasing awareness among security guards regarding the prevention of varicose veins. Keywords Varicose veins Security guards Security recruitment agency Information booklet